If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -8 = -6x + 13 Reorder the terms: -8 + X = -6x + 13 Reorder the terms: -8 + X = 13 + -6x Solving -8 + X = 13 + -6x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + X = 13 + 8 + -6x Combine like terms: -8 + 8 = 0 0 + X = 13 + 8 + -6x X = 13 + 8 + -6x Combine like terms: 13 + 8 = 21 X = 21 + -6x Simplifying X = 21 + -6x
| 15t-3=10 | | 120=4.7x | | Cx=196 | | X^5(x^2-3x+6)= | | b-2-b-2= | | 3(2y+5)+2y=-6 | | log(8x+5)=1+log(x-8) | | 9-3x=66x | | 3+2x+6x=75 | | -3(-x+5)=5(4+2x) | | 17x^2-6x=9 | | 24=-12c | | -7x+8-7x=-160 | | 2s-3=6s-11 | | C/49=196 | | 10x=9+x | | 52=-7x-4x+8 | | x=0.999999999999 | | 10x=9.9999999999999 | | 67+25h=350+25h | | 2y+5=7+2y-9 | | 50-4n=64-6n | | 6x+2(x-7)=26 | | 4c=196 | | 0=r^2-8.41 | | 4(4x-2)+3=-4 | | 2x+6=0+5x | | 5=t-4s | | -7+6x=5x-15 | | g^2=99990 | | a=8/5(h-96) | | 0j=0 |